Technology Blueprint : DuoLight / Siti Marliana Roslan - Roslan, Siti Marliana (2020)
UstheDuo Sdn. Bhd. is a technology based company which located in Shah Alam. It was founded by a group of friend with various type of educational background and work field. UstheDuo Sdn. Bhd. was lead by Siti Marliana Binti Roslan as the Chief Excecutive Officer and helped by four other directors. This company offers a product innovation as their main production activities. The company innovates an existing product into an innovative product that could solve customer’s needs. For the first product of UstheDuo Sdn. Bhd. they produce DuoLight.